Implementation of STEM-Based PjBL with Design Thinking Strategies to Improve Student’s Creative Thinking Skills on Global Warming Materials - Sari, Fitri Nur Indah; Abdurrahman, Abdurrahman; Ertikanto, Chandra (Radiasi : Jurnal Berkala Pendidikan Fisika, 2026)
This study aims to determine the effect of PjBL-STEM learning with design thinking strategies on students' creative thinking skills on global warming material. This research was conducted at public high school Pringsewu with a research design that is non-equivalent control group design. The research instrument used was a description test. Learning using PjBL-STEM with a design thinking strategy improves students' creative thinking skills, this is indicated by the average value of the experimental class N-gain of 0.6130 which is greater than the control class with an average value of 0.5051 N-gain which is in the moderate category. Based on this data, it shows that the creative thinking ability of students has a significant difference between the experimental class and the control class. This is also supported by the data from the Independent Sample t-test hypothesis test results obtained Sig value. 0.003, it can be decided that the application of PjBL- STEM with a design thinking strategy can improve students' creative thinking skills on global warming material.